Variation in floral morphology in a hybrid complex of Cyclamen in Sardinia. (2nd January 2019) - Papuga, Guillaume; Filigheddu, Rossella; Gauthier, Perrine; Farris, Emmanuele
ABSTRACT: Background : Hybridization is a key driver of plant speciation, and understanding ongoing hybridization provides insights into the underlying process. We studied a hybrid complex in Mediterranean Cyclamen between common C. repandum and rare C. balearicum on Sardinia. Aims : We analyzed variation in the frequency and morphology of different floral types to assess the degree of hybridization and analyze the ecological niche to better understand factors that influence the maintenance of hybrid populations. Methods : We recorded the frequency of the different flower color-types in 45 populations and measured floral traits in 10 of them. We characterized the spatial extent and climatic niche of this hybrid complex. We analyzed floral type variation in four traits (flower size, style and anther length, herkogamy). Results : Hybrid populations occupy a wide area on the NW coast of the island ( 1000km2). Sites dominated by hybrid floral types are ecologically marginal for the common parent. The C. repandum -like type is present in all populations and shows a decrease in style and anther length and herkogamy in populations containing a greater proportion of hybrids. Conclusions : This hybrid complex provides an ideal situation to examine reproductive isolation due to variation in the ecological niche of different floral types.